KINERJA KEUANGAN BERPENGARUH TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Putri Rundulemo; Muslichah muslichah (ITB AAS INDONESIA, 2024)
The objective of this study is to explore the effect of financial performance on firm value, with corporate social responsibility (CSR) as a moderating variable. The study focused on transportation companies listed in Indonesia Stock Exchange, with a sample size of 30 companies. The results indicate that financial performance has a positive effect on firm value. Furthermore, this research also found that CSR strengthens the influence of financial performance on company value. The findings suggest that transportation companies can enhance their firm value by improving their financial performance. Additionally, by actively engaging in Corporate Social Responsibility (CSR) activities, these companies can further amplify the positive impact of their financial success on their overall value. This implies that transportation companies should not only focus on financial metrics but also invest in CSR initiatives